Function of the anal sphincters after chronic radiation injury. Issue 5 (May 1986) - Varma, J S; Smith, A N; Busuttil, A
Abstract : Anorectal manometry was done in 10 men with chronic radiation proctitis and symptoms of urgency, frequency, and occasional incontinence of faeces. They were compared with 10 asymptomatic age and sex-matched controls. The maximum resting anal canal pressure and the physiological sphincter length were significantly lower (p less than 0.01) in the irradiated group. The rectosphincteric reflex was absent in one patient and showed abnormalities of recovery in four others, who had received radiotherapy. The squeeze pressure of the external sphincter was not significantly different. These results indicate that dysfunction of the internal anal sphincter may contribute to patients' anorectal symptoms after pelvic radiotherapy. Histological evidence suggests that damage to the myenteric plexus is mainly responsible. The manometric function of the external sphincter remains relatively unaffected.